2022
DOI: 10.1093/humrep/deac010
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the ageing paradigm in endometrium: endometrial gene expression related to cilia and ageing hallmarks in women over 35 years

Abstract: STUDY QUESTION Does age affect endometrial gene expression? SUMMARY ANSWER Using unsupervised artificial intelligence methods, we report for the first time that endometrial gene expression changes from 35 years of age in women. WHAT IS KNOWN ALREADY Female fertility declines with age, largely attributed to declining oocyte quality and ovarian reserve. Combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 73 publications
3
27
0
Order By: Relevance
“…In particular, AGR3 was among the top 10 up-regulated DEGs in the endometria of the patients with COVID-19, and the protein it codes for has been shown to be overexpressed in the endometrial ciliated luminal epithelium of women with recurrent implantation failure and recurrent pregnancy loss ( 48 ). Alterations in ciliated cells also occur in other reproductive disorders such as endometriosis ( 49 , 50 ). Further, these reports describe the alteration of ribosome and phosphorylation processes during an endometrial pathology ( 49 ), supporting our findings of these 2 mechanisms being up-regulated in our group of patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, AGR3 was among the top 10 up-regulated DEGs in the endometria of the patients with COVID-19, and the protein it codes for has been shown to be overexpressed in the endometrial ciliated luminal epithelium of women with recurrent implantation failure and recurrent pregnancy loss ( 48 ). Alterations in ciliated cells also occur in other reproductive disorders such as endometriosis ( 49 , 50 ). Further, these reports describe the alteration of ribosome and phosphorylation processes during an endometrial pathology ( 49 ), supporting our findings of these 2 mechanisms being up-regulated in our group of patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about the role of cilia in endometrial function, a recent single-cell study has identified both ciliated and non-ciliated epithelial cell populations ( Garcia-Alonso et al 2021 ). Transcriptomic studies have also highlighted a potential relevance for cilia function in the endometrium of women with endometriosis and that of women over 35 years ( Devesa-Peiro et al 2020 , 2022 ). Variants in genes linked to primary ciliary dyskinesia (DNAH11 and CCNO) are mutated in women with infertility, and gene variants identified from women with recurrent pregnancy loss were also related to cilia motility disorders ( Qiao et al 2016 , Maddirevula et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accompanying the morphological changes, molecular alterations also occur in the endometrium with age. A recent transcriptomic study of the endometrium of women over 35 and women under 35 years of age identified thousands of differentially expressed genes and noted a down-regulation of epithelial cell proliferation as well as an up-regulation of cilia-related processes ( 56 ). The mechanisms through which age-related morphological and molecular changes in the endometrium influence the endometrial receptivity in the WOI should be investigated further as it may contribute to the identification and optimization of implantation.…”
Section: Potential Mechanisms Regulating the Optimal Woimentioning
confidence: 99%